2020
DOI: 10.1111/jorc.12339
|View full text |Cite
|
Sign up to set email alerts
|

Body weight‐based initial dosing of tacrolimus in renal transplantation: Is this an ideal approach?

Abstract: Background Tacrolimus dosing immediately posttransplant is based on body weight. Recent studies have highlighted that the dosing of tacrolimus purely based on weight may not be appropriate, particularly in individuals who are obese. Objectives This study aimed to estimate the effect of body mass index (BMI) and the weight‐based dosing on tacrolimus trough levels in recipients of renal transplants. Design and Participants This study was conducted on 400 of the 863 patients registered in the Salford, UK, renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Patients with obesity often exhibit a body composition with higher adipose content, potentially leading to increased distribution of lipophilic drugs, such as tacrolimus. [27][28][29] In fact, overexposure from initial doses of tacrolimus has been observed in several studies of patients with obesity, [30][31][32][33][34] suggesting that dosing of tacrolimus in transplant recipients is not one size fits all and that body weight may play a significant role in initial doses and correlation to tacrolimus levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with obesity often exhibit a body composition with higher adipose content, potentially leading to increased distribution of lipophilic drugs, such as tacrolimus. [27][28][29] In fact, overexposure from initial doses of tacrolimus has been observed in several studies of patients with obesity, [30][31][32][33][34] suggesting that dosing of tacrolimus in transplant recipients is not one size fits all and that body weight may play a significant role in initial doses and correlation to tacrolimus levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such patients will require a lower tacrolimus dose per kilogram of body weight. Further, a recent study 20 questioned that weight‐based initial administration of tacrolimus in kidney transplantation is not an ideal regimen. Chinnadurai et al 20 found that patients with higher BMI required a significantly lower tacrolimus dose per kilogram of body weight when dosing was based on tacrolimus C 0 at months 1 and 6 after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Further, in patients receiving kidney transplantation, the concentration of TAC among obese patients (BMI>30 kg/m 2 ) was higher than that in non-obese patients, and obese patients were also subject to the risk of overexposure when the same dose of 0.15 mg/kg/day was administered. 28 …”
Section: Discussionmentioning
confidence: 99%